The relationship between secularism and democracy: The case of Turkey in the 2000s - Şar, Edgar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis offers a detailed analysis of the relationship between secularism and democracy, with particular reference to the case of Turkey. At a time when secularism is often associated with states’ non-egalitarian and exclusionary practices, this thesis puts forward the concept of “secularism as a political principle” and presents it as a sine qua non condition for a polity to be an inclusionary democracy. Furthermore, with a detailed examination of the relevant literature, this thesis indicates that there is a decent consensus among the prominent scholars in this field on the positive relationship between correctly implemented secularism and a state’s democratic credentials. In this regard, this thesis elaborates on the process of the “de-secularization of the state” in Turkey in the 2000s at the levels of ends, institutions, and law and policies and reveals that this process has so far gone hand in hand with increasing intensity of exclusion by the state and the domination of a particular comprehensive doctrine in the political sphere.
Keywords: Secularism -- Turkey.; Democracy -- Turkey.